KETIMPANGAN GENDER DAN BEBAN SOSIAL PEREMPUAN DALAM NOVEL DUA GARIS BIRU KARYA LUCIA PRIANDARINI - Purwati, Aisyah (PT. CASA CENDEKIA MEDIA, 2025)
This study aims to analyze gender inequality and the social burdens experienced by the female character in the novel Dua Garis Biru by Lucia Priandarini. The novel addresses the issue of teenage pregnancy outside of marriage and illustrates how the character Dara bears disproportionate social pressure, family expectations, and societal stigma compared to the male character, Bima. Using a descriptive qualitative approach and content analysis method, along with feminist literary criticism theory as the analytical framework, this research finds that gender inequality is reflected through practices of subordination, unequal social stigma, double burdens, and limited access to education. Dara's experiences highlight how women often become victims of double standards in a patriarchal society. These findings contribute to the discourse of feminism in contemporary Indonesian literature and encourage reflection on the importance of gender equality and social support for women.